Care standards for non-alcoholic fatty liver disease in the United Kingdom 2016: a cross-sectional survey. Issue 4 (28th April 2017) - Sheridan, David A; Aithal, Guru; Alazawi, William; Allison, Michael; Anstee, Quentin; Cobbold, Jeremy; Khan, Shahid; Fowell, Andrew; McPherson, Stuart; Newsome, Philip N; Oben, Jude; Tomlinson, Jeremy; et al.
Abstract : Objective: Guidelines for the assessment of non-alcoholic fatty liver disease (NAFLD) have been published in 2016 by National Institute for Health and Care Excellence and European Associations for the study of the Liver–European Association for the study of Diabetes–European Association for the study of Obesity. Prior to publication of these guidelines, we performed a cross-sectional survey of gastroenterologists and hepatologists regarding NAFLD diagnosis and management. Design: An online survey was circulated to members of British Association for the Study of the Liver and British Society of Gastroenterology between February 2016 and May 2016. Results: 175 gastroenterologists/hepatologists responded, 116 completing the survey, representing 84 UK centres. 22% had local NAFLD guidelines. 45% received >300 referrals per year from primary care for investigation of abnormal liver function tests (LFTs). Clinical assessment tended to be performed in secondary rather than primary care including body mass index (82% vs 26%) and non-invasive liver screen (86% vs 32%) and ultrasound (81% vs 37%).Widely used tools for non-invasive fibrosis risk stratification were aspartate transaminase (AST)/alanine transaminase (ALT) ratio (53%), Fibroscan (50%) and NAFLD fibrosis score (41%). 78% considered liver biopsy in selected cases. 50% recommended 10% weight loss target as first-line treatment. Delivery of lifestyle interventions was mostly handed back to primary care (56%). A minority have direct access to community weight management services (22%).Follow-up was favoured by F3/4 fibrosis (72.9%), and high-risk non-invasive fibrosis tests (51%). Discharge was favoured by simple steatosis at biopsy (30%), and low-risk non-invasive scores (25%). Conclusions: The survey highlights areas for improvement of service provision for NAFLD assessment including improved recognition of non-alcoholic steatohepatitis in people with type 2 diabetes, streamlining abnormal LFT referral pathways, defining non-invasive liver fibrosis assessment tools, use of liver biopsy, managing metabolic syndrome features and improved access to lifestyle interventions.